Low Altitude Thermal Survey by Means of an Automated Unmanned Aerial Vehicle for the Detection of Archaeological Buried Structures. Issue 4 (2nd July 2013) - Poirier, Nicolas; Hautefeuille, Florent; Calastrenc, Carine
ABSTRACT Airborne thermal prospecting is based on the principle that there is a fundamental difference between the thermal characteristics of buried remains and the environment in which they are buried. The French 'Archéodrone' project aims to combine the flexibility and low cost of using an airborne drone with the accuracy of the registration of a thermal digital camera. This combination allows the use of thermal prospection for archaeological detection at low altitude with high‐resolution information, from a microregional scale to the site scale. The first results have allowed us to assess the contribution of this technique for the detection of ancient roads, land plots boundaries, site plans and underground caves. Copyright © 2013 John Wiley & Sons, Ltd.